Non-ST-elevation acute coronary syndromes. Issue 2 (March 2015) - Moore, Cathy
Abstract : Coronary artery disease remains the leading cause of death worldwide, with 1 in 6 deaths occurring in the USA. Non-ST-elevated MI has a 50% pre-hospitalization mortality rate. Clinical presentations of a MI include: prolonged chest pain or pressure, nausea and/or vomiting, diaphoresis, pallor and anxiety. Some patients are at higher risk for a typical presentations, including: older adults, women, and patients with diabetes.